2022
DOI: 10.1021/acs.chas.1c00064
|View full text |Cite
|
Sign up to set email alerts
|

Toward Improved Safety Culture in Academic and Industrial Chemical Laboratories: An Assessment and Recommendation of Best Practices

Abstract: Numerous injuries and fatalities in chemical laboratories in the United States over the past few decades have suggested the need to take measures that go beyond mere compliance and toward promoting safer practices. A collaboration between the Center for Innovative and Strategic Transformation of Alkane Resources and Purdue Process Safety and Assurance Center assessed the current safety culture in chemical laboratories at their academic and industrial partners by conducting safety surveys. Key areas of improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…To address this gap, the National Science Foundation (NSF) encouraged and funded a joint effort between two research centers, Center for Innovative and Strategic Transformation of Alkane Resources (CISTAR) and Purdue Process Safety & Assurance Center (P2SAC), to investigate ways to improve safety practices in research laboratories and develop a tool that will assist with the hazard analysis process. An independent survey of safety practices, conducted with the help of industrial and academic laboratories involved with CISTAR and P2SAC, suggested that the continued occurrence of incidents is potentially linked to the lack of adequate documentation of best practices and the scarcity of tools that can help research laboratories quickly analyze and address safety risks . Equally important, from the Texas Tech laboratory explosion case study, the CSB cited the researchers’ ineffective assessment of the physical hazards and limited analysis of the issues arising during scale-up that contributed to the incident. , In so doing, the researchers’ assumptions concerning the relative safety of the small-scale reaction batch did not directly translate to the larger-scale setup.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this gap, the National Science Foundation (NSF) encouraged and funded a joint effort between two research centers, Center for Innovative and Strategic Transformation of Alkane Resources (CISTAR) and Purdue Process Safety & Assurance Center (P2SAC), to investigate ways to improve safety practices in research laboratories and develop a tool that will assist with the hazard analysis process. An independent survey of safety practices, conducted with the help of industrial and academic laboratories involved with CISTAR and P2SAC, suggested that the continued occurrence of incidents is potentially linked to the lack of adequate documentation of best practices and the scarcity of tools that can help research laboratories quickly analyze and address safety risks . Equally important, from the Texas Tech laboratory explosion case study, the CSB cited the researchers’ ineffective assessment of the physical hazards and limited analysis of the issues arising during scale-up that contributed to the incident. , In so doing, the researchers’ assumptions concerning the relative safety of the small-scale reaction batch did not directly translate to the larger-scale setup.…”
Section: Introductionmentioning
confidence: 99%
“…The property databases mentioned earlier can be used to understand the inherent hazards associated with the type of reaction system being studied. Despite access to these tools, our independent industrial survey noted certain challenges when using these tools to assess the risks involved in a specific experimental system . Some of these challenges include the inconvenience of accessing multiple tools and databases during hazard evaluation, the lack of a streamlined procedure for hazard evaluation, and the limited functionalities in major tools for chemical compatibility checks or PPE (personal protective equipment) guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Most published studies of chemical safety focus on hazards or incidents with individual chemicals or provide understanding of safety management practices in academic or industrial chemistry laboratories , but offer more limited insights into the importance of the physical environment, organizational power, and culture , in determining human behavior and chemical safety as determined in this study. The power imbalance between “work as imagined” and “work as done” bedevils compliance-based approaches to safety .…”
Section: Discussionmentioning
confidence: 99%
“…According to this survey, the KAP of teachers and laboratory technicians were below the standard level of science practitioners. Therefore, the authors have recommended the following intervention strategies to improve the KAP of teachers and laboratory technicians and promote a stronger lab safety culture formulated from this study as well as other past studies in different countries. , Teaching laboratory safety as part of a chemistry curriculum in secondary and preparatory schools is critical to preparing students for their future careers with a solid safety mindset. Teachers and laboratory practitioners play an essential role in modeling safety to their students.…”
Section: Recommended Remediating Strategiesmentioning
confidence: 99%